Afghanistan in Transition: POST 2014. - Rahimi, Abdul Waheed (ADA University, 2014)
It has been thirteen years since the crack-down of Taliban regime and Afghanistan is still suffering of economic and security problems. The insurgent groups under the names of Al Qaeda, Taliban, Haqqani network, Hizb e Islami and many other like-minded individual groups have been fighting against the Afghan and foreign troops in Afghanistan for different reasons. The main reason that all radical groups are agreed is to impose the fundamentalist interpretation of Islam and strictly implementation of Sharia law plus the pull-back of foreign troops. The support of international community from the ANSFs builds the trust among the people that reinstate of these radical groups are impossible unless accepting the Afghan constitution but it is also clear that their defeat is not possible on the battleground, neither the Afghan government nor the insurgent will be able to deliver a knockout blow. Thus, the review of COIN strategy and negotiation settlement between the two sides should be the priority for the next government to consider in order to bringing peace and stability in Afghanistan. A successful security transition would depend on a responsible strategy to deal with Taliban and the support of international community from ANSFs. At the same time the future political actor who is going to be elected in runoff election in June 14, 2014 will be the first ever political transition from one elected president to another one. The success of political transition is depending on wide participation of people in election similar to the first round turnout and the transparency of the process. By end of 2014, the donors intended to decline the foreign aid which is equal to 40 percent of the GDP and cover half of the national budget. The timeline of declining foreign aid is labeled as economic transition. The economic transition will decline the economic growth for the upcoming years. Similarly, it will affect the macroeconomic stability, increase poverty and unemployment. Conversely, the economic will continue to grow fairly if the government and international community invest further on potential sectors as mining and agriculture which have significant share in GDP and contributes further in creation of jobs opportunity. Improving education and building effective governance is also one of the key priorities for a successful economic transition
Keywords: Public and International Affairs; Afghanistan -- History--2014-; Afghanistan -- Social conditions--21st century.; Afghanistan -- Social life and customs--21st century.